Preparedness of Tanzanian health facilities for outpatient primary care of hypertension and diabetes: a cross-sectional survey - Dr. Robert Peck, MD; Janneth Mghamba, MD; Fiona Vanobberghen, PhD; Bazil Kavishe, MD; Vivian Rugarabamu, MD; Prof. Liam Smeeth, PhD; Prof. Richard Hayes, DSc; Prof. Heiner Grosskurth, PhD; Saidi Kapiga, MD (Elsevier, 2014)
Background: Historically, health facilities in sub-Saharan Africa have mainly managed acute, infectious diseases. Few data exist for the preparedness of African health facilities to handle the growing epidemic of chronic, non-communicable diseases (NCDs). We assessed the burden of NCDs in health facilities in northwestern Tanzania and investigated the strengths of the health system and areas for improvement with regard to primary care management of selected NCDs. Methods: Between November, 2012, and May, 2013, we undertook a cross-sectional survey of a representative sample of 24 public and not-for-profit health facilities in urban and rural Tanzania (four hospitals, eight health centres, and 12 dispensaries). We did structured interviews of facility managers, inspected resources, and administered self-completed questionnaires to 335 health-care workers. We focused on hypertension, diabetes, and HIV (for comparison). Our key study outcomes related to service provision, availability of guidelines and supplies, management and training systems, and preparedness of human resources. Findings: Of adult outpatient visits to hospitals, 58% were for chronic diseases compared with 20% at health centres, and 13% at dispensaries. In many facilities, guidelines, diagnostic equipment, and first-line drug therapy for the primary care of NCDs were inadequate, and management, training, and reporting systems were weak. Services for HIV accounted for most chronic disease visits and seemed stronger than did services for NCDs. Ten (42%) facilities had guidelines for HIV whereas three (13%) facilities did for NCDs. 261 (78%) health workers showed fair knowledge of HIV, whereas 198 (59%) did for hypertension and 187 (56%) did for diabetes. Generally, health systems were weaker in lower-level facilities. Front-line health-care workers (such as non-medical-doctor clinicians and nurses) did not have knowledge and experience of NCDs. For example, only 74 (49%) of 150 nurses had at least fair knowledge of diabetes care compared with 85 (57%) of 150 for hyptertension and 119 (79%) of 150 for HIV, and only 31 (21%) of 150 had seen more than five patients with diabetes in the past 3 months compared with 50 (33%) of 150 for hypertension and 111 (74%) of 150 for HIV. Interpretation: Most outpatient services for NCDs in Tanzania are provided at hospitals, despite present policies stating that health centres and dispensaries should provide such services. We identified crucial weaknesses (and strengths) in health systems that should be considered to improve primary care for NCDs in Africa and identified ways that HIV programmes could serve as a model and structural platform for these improvements. Funding: UK Medical Research Council.